Autumnal N storage determines the spring growth, N uptake and N internal cycling of young peach trees - Jordan, Marie-Odile; Wendler, Renate; Millard, Peter (Trees (Berlin, West), 2012)
Although N storage determines early spring growth in trees, the usefulness of autumn N supply remains unclear as N uptake decreases in autumn, but could be restored earlier in spring to compensate for low N cycling. We intended here to evaluate the effects of autumn N supply on N uptake, storage and cycling, and spring growth. Four levels of N fertilisation were applied to 1-year-old peach trees, between the end of shoot growth and leaf fall. In spring, N supply was 15 N labelled. Organ dry weights and concentrations of 14 N, 15 N, starch and soluble sugars were evaluated after the first growth flush. Bud development had previously been described in the same trees by Jordan et al. (Trees-Struct Func 23:235–245, 2009 ). Fertilisation promoted autumn N uptake, spring N uptake and growth up to a threshold level, since no differences were evidenced between the three highest N treatments. The variability in tree 14 N contents was related to the number of phytomers per tree in autumn, i.e. to tree size. In spring, the depletion of the perennial structures was independent of treatment, indicating a complete mobilisation of the N stores. Spring growth was related to the amounts of cycling N, and spring N uptake was in turn proportioned to shoot and fruit growth. The lower N uptake of the N limited trees was not due to a C shortage since these trees displayed the highest starch concentrations. We conclude that a moderate autumn fertilisation improved spring growth and fruit production (Jordan et al. in Trees-Struct Func 23:235–245, 2009 ) and that a deficit of N storage could not be compensated for by an increase in spring N uptake.